Program Pengembangan Kemampuan Soft Skills bagi Karangtaruna di Kelurahan Wonoplumbon, Kecamatan Mijen, Kota Semarang - Eko Nursanty; Agus Wibowo; Rahmad Purwanto; Putra Inter Perdana Waruwu (Universitas 17 Agustus 1945 Semarang, 2023)
Soft skills are non-technical skills that relate to how people operate, engage with coworkers, solve problems, and manage the task for which they are responsible. Soft skills are required for future leadership jobs and will influence their effectiveness in managing teams to execute diverse initiatives. Furthermore, the capacity to show attentiveness and empathy to clients indicates a dedication to solving problems or meeting their requirements. To strengthen the ability to work with others and positively impact one's profession, a soft skills development program was held for the community in Wonoplumbon Urban Village, Mijen Sub-district, Semarang City, and its stakeholders comprising of RW leaders. This activity aims to achieve one of the Sustainable Development Goals, namely that governments, workers' organizations, and employers all over the world work to improve workers' employability, place young people in decent productive jobs, and increase company productivity through higher quality and relevant training.